Improving Science Learning Outcomes for Class V SD Negeri 7 Watopute Through Direct Instruction Models with Cooperative Learning Approach - Sitti Darni (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2021)
This study aims to determine the extent to which the success rate of students in the learning process through a cooperative learning approach, especially in science subjects. This study uses a direct learning model (direct instruction) to overcome problems that occur in the learning process for students. The issues in this study were 23 fifth-grade students at SDN 7 Watopute. To achieve the results by what the researchers expected, the researchers carried out II (two) cycles of 4 (four) meetings for approximately 2 (two) months. The results of the description analysis revealed that through the direct instruction model approach in science learning in cycle I (one), the average score of students was 6.09, and learning completeness reached 39.13%.In contrast, in cycle II (two), the average value was the average student is 7.91 and learning completeness reaches 78.26%. The learning atmosphere changed from what seemed dull to being so fun. Likewise, the level of student activity becomes higher. Students are enthusiastic about participating in the learning process; no one looks lazy. Thus, it can be concluded that there is a significant effect on increasing students' learning abilities through a cooperative learning approach in the direct instruction model in science learning for class V SDN 7 Watopute